AI in Social Media Marketing : Opportunities and Challenges - Ms. Anshu; Dr. Monika Sharma (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
Using artificial intelligence (AI) technology to improve brand engagement, targeting accuracy, and content personalisation, social media marketing (SMM) has undergone tremendous evolution. In order to highlight the transformational power of AI through computer vision, natural language processing (NLP), and predictive analytics, this article investigates how AI is integrated into SMM. Artificial intelligence (AI) has revolutionised the way businesses engage with their consumers by enabling more granular customer data, tailored marketing strategies, and streamlined operations. Even with its benefits, AI in SMM has drawbacks such algorithmic bias, data privacy, and ethical issues. This paper offers a thorough review of AI’s involvement in SMM, highlighting both opportunities and challenges, by looking at successful implementations and lessons learnt from mistakes.